Acute Toxicity of Keladi Tikus (Typhonium flagelliforme (Lodd.) Blume) Ethanol Extract on Zebrafish (Danio rerio) Embryo In Vivo - Fajar Fakri; Loly Subhiaty Idrus; Maria Alexandra Iskandar; Indra Wibowo; I Ketut Adnyana (Indonesian Journal of Pharmacy, 2020)
Keladi tikus (Typhonium flagelliforme (Lodd.) Blume) is an Indonesian medicinal plant that has various pharmacological properties. Zebrafish (Danio rerio) has been proposed as a model that can bridge the gap between cell assays and rodent assays. Evaluation of the toxic effects of natural products using the Zebrafish model can be assessed starting from the blastula stage of embryonic development. This study aims to investigate the potential acute toxicity effect of keladi tikus-ethanol extract (KTEE) using zebrafish embryos. A static non-replacement regime for acute toxicity testing was used. Wild-type zebrafish embryos were exposed to various concentrations of KTEE (50, 100, 200, 400, 800, 1600 µg/mL) starting at 6 hours post-fertilization (hpf) until 96 hpf. The results showed that the survival rate of zebrafish embryos decreased as the concentration of the test extract increased. The LC50 values of KTEE were 494.553 µg/mL at 96 hpf and 555.787 µg/mL at 72 hpf. Embryotoxicity effect of KTEE includes hatching delays and decreased heartrate on zebrafish embryos, especially at high concentrations. KTEE also caused abnormalities in embryo morphology, including pericardial edema, jaw and tail deformity.